The Drives behind Sport Commitment among Soccer Players under the Age of (17) in the Hashemite Kingdom of Jordan (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed at identifying the drives behind sport commitment among the junior soccer players under the age of (17) as well as finding out the impact of the player's age and their training age. The researcher used the descriptive survey approach. The study sample consisted of (76) soccer players who are joining (5) Jordanian clubs, where the clubs were chosen by the random regular way from the records of the Jordanian federation of football. The soccer players were chosen purposively, and they represent the meantcategory. The study used the scale of sport commitment developed by Scanlan et al., (2016), where the researcher verified arbitrators' validity of the scale, after translating it, and its reliability coefficient was found to be (0.97) by using test-pretest methods. In order to analyze the results of the study, the following statistical methods were used: means, standard deviations, Kruskal-Wallis Test, and Mann-Whitney test.The results showed that the overall level for the domains was within the level of "agree", as it represented the mean of all the domains. As for domains, the results revealed that the third domain (sport enjoyment) gained the first motive among the study samples, as it represented the most important motive of sport commitment among soccer players. The results revealed that there are no statistically significant differences between the first age group (less than 14) and the second age group (14-17). The results revealed that there are no statistically significant differences between the variable of sport commitment and the player's training age. The study recommended the necessity of focusing on measuring the level of sport enjoyment and commitment among the age group (14-17) years old for the distinguished players in order to maintain their development  and progression
Keywords: Drives; Sport Commitment; Soccer Players under the age of (17) years old.